The second digital transition: to the mobile space — an analysis of Europeana. Issue 4 (1st October 2013) - NICHOLAS, David; CLARK, David
ABSTRACT: According to industry estimates the mobile device (smartphone and tablet) will soon be the main platform for searching the Web and yet our knowledge of how mobile consumers use information – especially scholarly information, and how that differs from desktop or 'tethered' users – is imperfect to say the very least. This article aims to correct this through an analysis of the usage logs of a major cultural, multimedia website, Europeana.eu, which started tackling the mobile challenge in 2011. The challenges of identifying mobile use – no easy matter – are described. The information behaviour of 150, 000 mobile users is examined and compared with that for desktop users. The main findings are that mobile users are the fastest‐growing user community and that their visits are very different in the aggregate from those arising from desktops. Mobile visits are information 'lite': typically shorter, less interactive, and with less content viewed per visit. Use takes on a social rather than office rhythm, with use peaking at nights and weekends.